El avance de las nuevas tecnologías y su incidencia en el desarrollo de las actividades de los docentes del Colegio Nacional Atahualpa, de la ciudad de Machala, período 2013-2014. - Alvarado Saavedra, Ariana Rosmeri (2014)
The research process allowed to reach conclusion that teachers of Atahualpa National College are not correctly applying Information Technology and Communication ICT in the teaching-learning process due to lack of training and preparation of new technologies, which is severely impacting in students because they are not being uneven to adapt to the modern world.